Material matters : developing business for a circular economy - Rau, Thomas (Architect); Oberhuber, Sabine (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Our planet is a closed system with limited material resources, yet our current economic model is designed in a one-way direction from resource extraction to disposal, leading to resource depletion. This book proposes a new economic model, offering an alternative to this linear 'take-make-waste' economy. Material Matters shows a way of creating a circular economy by using the unlimited resources we have: renewable energy, data and intelligence. It describes a system based on circular business models centred on selling performance rather than ownership, designing products and buildings as resource banks, and equipping products with a 'material passport' to ensure their usability for future generations. Businesses thereby become custodians of materials, rather than consumers of materials and sellers of products. The book evokes the vision of a radically new economic model based on a compelling narrative, supported with cases that have been developed in conjunction with major companies, for example, convincing Philips to sell light instead of lamps, saving energy and materials by creating a whole new business model, a case which has become iconic for the circular economy. Material Matters is not a sombre analysis of the state of the planet but a concrete and comprehensive agenda for change, offering perspectives for taking action for business and individual consumers alike"--
Introduction -- The product-as-problem -- The linear economy or the end of the line -- Spaceship Earth -- a closed system -- Permanent temporality -- Changing the rules of the game -- The Material Passport -- Madaster -- a registry for materials -- UDMR, The Universal Declaration of Material Rights -- Material-as-a-Service -- rethinking material ownership -- Completing the Copernican Revolution.
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable development; Circular economy; Environmentalism -- Economic aspects; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Green Business; BUSINESS & ECONOMICS / Consumer Behavior